Designing Immersive Learning Experiences: A Postmortem Analysis of a VR Game for Teaching Programming - Avellar, Gustavo Martins Nunes; Aragão, Paulo André Pimenta; Generich, Fernando Henrique Paes; Villela, Pedro Lunkes; Castro, Lucas Oliveira; Barbosa, Ellen Francine (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento Digital, 2025)
Introduction: Teaching programming concepts through immersive environments has demonstrated pedagogical potential, although most existing solutions rely on expensive technologies that remain unaffordable in many educational contexts. Objective: This paper presents a postmortem analysis of the design, development, and evaluation of SSPOT-VR, an affordable, collaborative VR mobile game developed to support the teaching and learning of programming for K-12 students. Methodology: We adopted a postmortem analysis approach grounded in the game development literature, supported by user evaluations and continuous reflection throughout iterative development phases. Results: The analysis highlights strengths, including multiplayer design, visual storytelling, and accessible deployment, while also identifying challenges related to infrastructure, usability, and scalability. Lessons learned informed design enhancements and future directions, such as cross-platform support and strategies for pedagogical integration.